Microsoft Azure Data Engineer Associate (DP-203) Cert Prep: 4 Monitor and Optimize Data Storage and Data Processing by Microsoft Press. - Warner, Tim; Press, Microsoft (linkedin.com, 2023)
Explore the concepts and skills required to monitor and optimize data storage and data processing to pass the Microsoft Azure Data Engineer Associate (DP-203) certification exam.